Предмет: Алгебра,
автор: asurpv
Вычисли, представив в виде суммы или разности множители, используя формулу a2 – b2 = (a – b)(a + b).
Ответ: 72 ∙ 68 = (
+ 2)(
– 2) =
–
=
.
AbuBlitz:
72*68=(70+2)(70-2)=70^2-2^2=4896
Ответы
Автор ответа:
108
Ответ:
72*68=(70+2)(70-2)=70^2-2^2=4896
Объяснение:
^2 - это степень
Похожие вопросы
Предмет: Русский язык,
автор: verynuanet
Предмет: Химия,
автор: TOLЯН
Предмет: Физика,
автор: dragovich1
Предмет: Математика,
автор: Thefondue555
Предмет: Литература,
автор: boltacheva1987